2013
DOI: 10.1073/pnas.1214168110
|View full text |Cite
|
Sign up to set email alerts
|

Histone methyltransferase MLL3 contributes to genome-scale circadian transcription

Abstract: Daily cyclical expression of thousands of genes in tissues such as the liver is orchestrated by the molecular circadian clock, the disruption of which is implicated in metabolic disorders and cancer. Although we understand much about the circadian transcription factors that can switch gene expression on and off, it is still unclear how global changes in rhythmic transcription are controlled at the genomic level. Here, we demonstrate circadian modification of an activating histone mark at a significant proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 35 publications
4
115
6
Order By: Relevance
“…Although the central circadian clock, as indexed by melatonin, remained largely unaffected, the temporal organization of expression of clock genes considered to be central to circadian rhythm generation was affected in the blood transcriptome, with only NR1D2 and CSNK1E remaining rhythmic when sleeping out of phase. Histone modification, and the control of transcription and translation (4)(5)(6)(7)(8)(9), is also considered central to circadian organization of the transcriptome and the time courses of transcripts associated with all of these processes were affected in this study (Fig. 3).…”
Section: Transcripts and Associated Molecular Processes Affected By Dmentioning
confidence: 72%
“…Although the central circadian clock, as indexed by melatonin, remained largely unaffected, the temporal organization of expression of clock genes considered to be central to circadian rhythm generation was affected in the blood transcriptome, with only NR1D2 and CSNK1E remaining rhythmic when sleeping out of phase. Histone modification, and the control of transcription and translation (4)(5)(6)(7)(8)(9), is also considered central to circadian organization of the transcriptome and the time courses of transcripts associated with all of these processes were affected in this study (Fig. 3).…”
Section: Transcripts and Associated Molecular Processes Affected By Dmentioning
confidence: 72%
“…Alternatively, given that our results were obtained in a cellular context rather than in vitro chemical shift perturbation studies (14), it is possible that additional coactivators bound to dpCLK: dpBMAL1 also compete with dpCRY2 for binding. Histonemodifying enzyme orthologs of MLL and JARID1a, which are recruited at CLOCK:BMAL1, or proteins that recruit the transcriptional machinery are all potential candidates (34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, many studies reported histone modifiers and remodelers as part of the clockwork machinery, such as the histone acetyltransferase (HAT) p300 (Etchegaray et al 2003), the histone methyltransferases MLL1 (Katada and Sassone-Corsi 2010), and MLL3 (Valekunja et al 2013). The CLOCK protein itself was reported to show HAT activity (Doi et al 2006).…”
Section: Transcriptional Regulation Of Clock Controlled Genesmentioning
confidence: 99%